Moisture Effect on Characteristics of Slowly Digestible Potato Starch Prepared under Electron Beam Irradiation - Vinh Tien Nguyen; Loc Nguyen Thi; Khanh Son Trinh (Journal of Chemistry)
This study evaluates the effect of initial moisture contents (11.74–29.84%) on physicochemical changes, in vitro and in vivo digestibilities of potato starch irradiated with electron beam (EB). After a constant dose of EB irradiation, intrinsic viscosity and average molecular weight of potato starch decreased for all investigated moisture contents. When the moisture of starch was lower than 18%, the depolymerization predominated, hence increasing the amylose content. At higher moisture, water can strongly absorb EB and produce highly active species that induced the crosslinking of amylose molecules and the disruption of large crystals into smaller defective crystals. As a result, we found a maximum in amylose content at 14.84% moisture and a minimum in the degree of crystallinity at 17.5% moisture. Thermal stabilities between the irradiated samples were not significantly different. In vitro digestibility results showed that higher moistures during EB treatment induced structural changes that led to the conversion of resistant starch (RS) fraction into slowly digestible starch (SDS). Moreover, an in vivo digestive model in mice showed that EB-treated starch was able to maintain blood glucose at a stable level for a long time. This study showed a potential for SDS production from potato starch using EB irradiation technology, even in large scale.